2021
DOI: 10.1515/med-2021-0368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of late-onset hemorrhagic cystitis on PFS after haplo-PBSCT

Abstract: Introduction This study is to investigate the effect of late-onset hemorrhagic cystitis (LOHC) on progression-free survival (PFS) of patients after haploidentical peripheral blood hematopoietic stem cell transplantation (haplo-PBSCT). Methods This retrospective study enrolled 74 patients with hematological malignancies treated with a myeloablative conditioning regimen and haplo-PBSCT. The effect of LOHC on PFS was studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previously, we showed that the incidence of LOHC increased after haplo-PBSCT, but LOHC had no significant effect on the progression-free survival (PFS) of patients after transplantation (14). Here, in this study, we further investigated the incidence of LOHC and the effect of LOHC on PFS of patients with acute leukemia after haplo-PBSCT using 5-year single-center data.…”
Section: Introductionmentioning
confidence: 94%
“…Previously, we showed that the incidence of LOHC increased after haplo-PBSCT, but LOHC had no significant effect on the progression-free survival (PFS) of patients after transplantation (14). Here, in this study, we further investigated the incidence of LOHC and the effect of LOHC on PFS of patients with acute leukemia after haplo-PBSCT using 5-year single-center data.…”
Section: Introductionmentioning
confidence: 94%